Toward Achieving a Vaccine-Derived Herd Immunity Threshold for COVID-19 in the U.S. - Gumel, Abba B.; Iboi, Enahoro A.; Ngonghala, Calistus N.; Ngwa, Gideon A. (Frontiers in Public Health, 2021)
The novel coronavirus (COVID-19) continues to inflict unprecedented public health and economic burden in all nooks and corners of the world. Although the control of COVID-19 has focused on the use of basic public health measures (such as quarantine, isolation, social-distancing, face mask usage and lockdowns), three safe and highly-effective vaccines (by AstraZeneca Inc., Moderna Inc. and Pfizer Inc.) have been approved for use in humans since December 2020. We present a new mathematical model for assessing the population-level impact of these vaccines. The model stratifies the total population into two subgroups, based on whether or not they wear face masks in public. The model is parametrized using COVID-19 mortality data for the third wave of the COVID-19 pandemic in the U.S. An expression for the vaccine-derived herd immunity threshold, is derived. Numerical simulations of the model show that the size of the initial proportion of individuals in the masks-wearing group, together with positive change in behaviour from the non-mask wearing group (as well as those in mask-wearing group do not abandon their masks-wearing habit) play a crucial role in effectively curtailing the COVID-19 pandemic in the U.S. This study further shows that the prospect of achieving herd immunity using any of the three currently-available vaccines, is quite promising. In particular, while the use of the AstraZeneca vaccine will lead to herd immunity in the U.S. if at least 80%of the populace is vaccinated, such herd immunity can be achieved using either the Moderna or Pfizer vaccine if about 60% of the U.S. population is vaccinated. Furthermore, the prospect of eliminating the pandemic in the US in the year 2021 is significantly enhanced if the vaccination program is complemented with nonpharmaceutical interventions at moderate increased levels of compliance (in relation to their baseline compliance). The study further suggests that, while the waning of natural and vaccine-derived immunity against COVID-19 induces only a marginal increase in the burden and projected time-to-elimination of the pandemic, adding the impacts of the therapeutic benefits of the vaccines into the model resulted in a dramatic reduction in the burden and time-to-elimination of the pandemic.